Relationship Maternal Characteristics (Parity And Age) With The Length of Time For Labor During The First And Second Stages of Labor at RSUD dr. R. Koesma Tuban - Dwi Kurnia Purnama Sari; Miftahul Munir; Tiara Putri Ryandini (Jurnal MIDPRO, 2021)
One of the important social indicators to measure the success of maternal mortality eradication programs and to see the status of maternal health is the Maternal Mortality Rate (MMR). The results of the initial survey in 2019 were 184 who experienced periods I and II, while in 2020 there were 222 people. The purpose of this study was to determine the relationship maternal characteristics (parity and age) with the length of time for labor during the first and second stages of labor at RSUD dr. R. Koesma Tuban. The research design used an analytical method with a cross-sectional research design. The population used was all mothers who gave birth in the maternity room at RSUD dr. R. Koesma Tuban in 2021 many 842 respondents, obtained a sample size of many 271 respondents. The sampling technique uses simple random sampling. Data collection uses secondary data, namely the independent and dependent variables. While the test used is chi-square with a significant level α = 0.05. The results showed that almost all of the results of the study showed that the length of time of delivery for the first and second stages of the primiparous tended to give birth accordingly, whereas in multiparous and grade multi the delivery was appropriate. Based on the chi-square test, it was found that x2 count = 5.705 ˃ x2 table = 3.841, then H0 was rejected H1 accepted This means that there is a relationship between maternal characteristics (parity and age) and the length of time for labor during the first and second stages of labor at RSUD dr. Koesma Tuban. From the research, it can be concluded that the characteristics of the mother (parity and age) can affect the length of time of stages I and II. One of the preventive efforts that can be done is to provide counseling about the ideal age for marriage, especially for women, regular antenatal examinations, counseling on family planning programs that can be used for married women under 20 years old and women over 35 years old.